2014
DOI: 10.1007/s00277-014-2053-9
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human erythropoietin in very elderly patients with myelodysplastic syndromes: results from a retrospective study

Abstract: Myelodysplastic syndromes (MDS) are common in elderly patients. Recombinant human erythro-poietin (rHuEPO) has been widely used to treat anemia in lower risk MDS patients, but few data are known about rHuEPO treatment in the very elderly patient group. In order to investigate the role of rHuEPO treatment in terms of response, overall survival (OS), and toxicity in a very elderly MDS patient group, 93 MDS patients treated with rHuEPO when aged ≥80 years were selected among MDS cases enrolled in a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Moreover, Hb increase translates to the amelioration of the quality of life and the increased overall survival of these patients [ 2 , 35 , 36 , 37 ]. In our opinion, the fact that, after 24 weeks, 83% of our patients can reach this safety threshold is additional proof of the effectiveness of erythropoietin zeta in the treatment of low/int-1-risk MDS patients, in line with data from real-life experiences [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, Hb increase translates to the amelioration of the quality of life and the increased overall survival of these patients [ 2 , 35 , 36 , 37 ]. In our opinion, the fact that, after 24 weeks, 83% of our patients can reach this safety threshold is additional proof of the effectiveness of erythropoietin zeta in the treatment of low/int-1-risk MDS patients, in line with data from real-life experiences [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 64%
“…By contrast, the serum ferritin levels were found to discriminate the probability of anemia response in transfusion‐independent patients, which constituted the largest group in our series. Although there is no prior information on the potential influence of serum ferritin levels on the response to ESA treatment in MF, high ferritin levels have recently been associated with a lower probability of response to ESA in patients with myelodysplastic syndromes . With regard to the other two independent risk factors identified in multivariate analysis, female patients had also a higher response rate to ESA in two prior studies in MF, whereas the leukocyte counts were higher in anemia responders in one study, although such difference did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 88%
“…Most studies were conducted in Europe (n = 24), and seven studies did not report the geographic location. Data sources were spread across nationwide registries, medical records in hospitals, Of the 38 studies identified (Table 2), one (3%) was a randomized controlled trial [22], three (8%) were non-randomized trials [23][24][25], 10 (26%) were single-arm trials [26][27][28][29][30][31][32][33][34][35], 15 (39%) were retrospective cohort studies [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], and four (11%) were prospective cohort studies [51][52][53][54]. One study (3%) was a compassionate, open-label, therapeutic trial [55], and four studies (11%) did not report the study design [56][57][58][59].…”
Section: Slrmentioning
confidence: 99%
“…The median age of the study population ranged from 63.1 years [57] to 82.7 years [39], with 25 studies having patients with a median age of >70 years (Table 3). In the 33 studies that reported biological sex, 42% to 74% of participants were male.…”
Section: Slrmentioning
confidence: 99%
See 1 more Smart Citation